New challenges to the implementation of active learning methods at Secondary schools in Kambata Tambaro zone, Ethiopia - Telore, Tesfanesh; Damtew, Abebe (JEES (Journal of English Educators Society), 2023)
The main objective of this study was to find out key factors which affect implementation of active learning methods at secondary schools in Kambata Tembaro zone, Ethiopia. The study was done on the bases of a descriptive survey design. Data sources for the study were 37 English language teachers. Questionnaire and focus group discussion were employed as data collecting tools. Both quantitative and qualitative techniques of data analysis were implemented. Thus, data collected through questionnaire were analyzed using SPSS and data gathered via group discussion were thematically analyzed. Findings of the study revealed that lack of motivation and interest among teachers to fully accomplish their role in teaching, students’ preference of illegal migration than attending school and unsuitable conditions in and around the classroom were the most challenging factors which affected implementation of active learning methods in the schools. It is recommended by the researchers that the government of Ethiopia should take immediate action to facilitate basic needs for the teachers. None Government and Government offices in the zone should work in collaboration to create awareness to the students and their parents on the bad effect of illegal migration. Students, parents, teachers and school administrators at woreda and zone level should deal together to help students achieve their objective of learning by improving the teaching learning habit in the zone. HIGHLIGHTS: The major factors that affect the implementation of active learning in secondary schools in the Kambata Tembaro zone. Implementation of active learning in the Kembata Tembaro zone is strongly affected by Teachers’ reluctance, lack of interest and motivation among students, unsuitable school conditions (number of students, shortage of teaching materials). The challenges identified include teachers' knowledge, skills, and attitudes, as well as classroom size, sitting arrangement, and availability of materials.